Wykorzystanie systemów informacyjnych w procesie podejmowania decyzji - Łapińska, Anna (The Use of Information Systems in the Process of Decision Making, 2006)
An attempt to improve cost and effect analysis in the milk processing industry has been discussed in this article. Empirical research has been conducted in the selected milk processing big, medium and little cooperative facilities in order to estimate the use of information gathered in the costs and revenue analysis in managing an economic unit on competitive market. Financial assessment of the modernization process in the integrated facilities has also been conducted. The author proposes: the use of multi-dimensional, multi-level and multi-group cost and effect analysis in reference with the information management's needs, to apply concentration stategies in the milk industry which will allow acquisition of capital to modernize and develop the integrated economic subject.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 252-261